2013
DOI: 10.1007/s11666-013-9999-3
|View full text |Cite
|
Sign up to set email alerts
|

Metal Matrix Composite Coatings Manufactured by Thermal Spraying: Influence of the Powder Preparation on the Coating Properties

Abstract: International audienceThe purpose of this study is to manufacture metal matrix composite coatings by thermal spraying. In order to improve coating's mechanical properties, it is necessary to increase homogeneity. To meet this objective, the chosen approach was to optimize the powder morphology by mechanical alloying. Indeed, the mechanical alloying method (ball milling) was implemented to synthesize NiCr-Cr3C2 and NiCrBSi-WC composite powders by using cold spraying and high-velocity oxygen fuel process, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In general, the graphite has poor wettability onto the Al and Mg surface and the angle ranges from 140 to 160 (Figure 15) 165,166 The technique applied for the fabrication of carbonaceous reinforced metal matrix nano-composites is Powder metallurgical process, 167,168 Thermal spraying, 169 and electrochemical deposition process 170 and liquid metallurgy. 171 Now each of the processes can be subclassified into laser deposition, metal infiltration and liquid metal stirrer processing for liquid metallurgy.…”
Section: Processing Techniquesmentioning
confidence: 99%
“…In general, the graphite has poor wettability onto the Al and Mg surface and the angle ranges from 140 to 160 (Figure 15) 165,166 The technique applied for the fabrication of carbonaceous reinforced metal matrix nano-composites is Powder metallurgical process, 167,168 Thermal spraying, 169 and electrochemical deposition process 170 and liquid metallurgy. 171 Now each of the processes can be subclassified into laser deposition, metal infiltration and liquid metal stirrer processing for liquid metallurgy.…”
Section: Processing Techniquesmentioning
confidence: 99%
“…The metal matrix composites exhibit high strength and improved wear resistance over the base metals. Previous studies have shown that the method of deposition plays a key role in governing the wear resistance behavior of metal-matrix composite coatings [18][19][20][21]. However, most of the studies reported the metal matrix composites based on tungsten-carbide or chromium-carbide, while the limited literature is available related to nickel-based cermet coatings.…”
Section: Introductionmentioning
confidence: 99%
“…As the friction and wear only occur on the surfaces of components, surface strengthening for 16Mn steels is a more cost-effective approach. Conventional surface treatment techniques, such as thermal spraying [1], cold spraying [2], physical vapor deposition [3], and chemical vapor deposition [4], have been reported to be feasible methods of improving the surface properties of the steel substrate by depositing high-performance coatings on its surfaces. Additionally, these coatings were also shown to have high hardness and excellent corrosion and wear resistance, but they are susceptible to being detached from the substrate in aggressive wear working conditions because of the mechanical bonding between them and the substrate.…”
Section: Introductionmentioning
confidence: 99%